Research progress on the mechanism of propofol in regulating autophagy - Xiao-Shuang ZHANG; Li-Li YANG; Ya-Ying XIE (Yixue xinzhi zazhi)
Autophagy is a process in which intracellular lysosomes are involved in the degradation of damaged organelles or macromolecular substances. In the physiological state, eukaryotic cells maintain tissue homeostasis through a low degree of autophagy. In recent years, many studies have shown that autophagy is involved in the pathophysiological disease processes caused by ischemia and hypoxia. As a commonly used intravenous an-esthetic, propofol is widely used in various types of surgery. Recent studies have shown that propofol plays a protective role by inhibiting autophagic cell death induced by ische-mia/reperfusion and hypoxia/reoxygenation. Meanwhile, other studies have shown that propofol can activate autophagy and have an anti-tumor effect. Current studies on the regulation of autophagy by propofol, involve AMPK/mTOR, Bcl/Beclin, Ca2+, miRNA and other cell signaling pathways. Based on the latest research, this paper reviews the mechanisms of propofol regulation of autophagy.